MAKING VIRGIN COCONUT OIL (VCO) USING THE ENZYMATIC METHOD - Melanda Niuwa (Jurnal Ilmiah dr. Aloei Saboe, 2022)
Virgin Coconut Oil (VCO) is one of the food sources of fat that is currently in great demand by people because of its health benefits, VCO has several advantages, namely high lauric acid content. Pure coconut oil contains ± 10% unsaturated fatty acids and ± 90% saturated fatty acids. The saturated fatty acid in VCO is lauric acid. Lauric acid is a medium chain fatty acid known as MCFA (Medium Chain Fatty Acid). Lauric acid and short chain saturated fatty acids can be beneficial for health to improve and moisturize skin conditions. This study aims to see how to make VCO by enzymatic method using papain enzyme from papaya fruit peel. The method used is the enzymatic method using the papain enzyme of papaya fruit peel where the process of making VCO is enzymatically using the papain enzyme from papaya sap. Papain catalyzes a substrate through a hydrolysis reaction with the help of water molecules. The results showed that there were three layers with the blondo layer and the oil being slightly mixed, which was caused by the ripe papaya skin, where the papain enzyme content was slightly reduced compared to the young papaya skin.